A quality systems study on FF international and Manufacturing Corporation - Herce, Cynee Rachel; Parilla, Liza. (Diliman, Quezon City College of Engineering, 1996)
quality audit was conducted by the group in FFI International Manufacturing Corporation in order to assure that the company quality policies are adequate and are being well carried out. As a result of the audit, the following problems were discovered: improper design and inadequate form, job tickets not fully utilized, deadlines can take precedence over quality, lack of problem tracking statistical analysis, lack of coordination, and lack of orientation of top management to quality. Thus the group suggests solutions to these problems, solutions such as: new form, trainings, process capability study and a proposal on an implementation plan to ensure the company's continuous improvement.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: FF International and Manufacturing Corporation; Manufacturing Industry; Quality control